Prokaryotic extracellular enzymatic activity in relation to biomass production and respiration in the meso- and bathypelagic waters of the (sub)tropical Atlantic - Baltar, Federico; Aristegui, Javier; Sintes, Eva; Van Aken, Hendrik M.; Gasol, Josep M.; Herndl, Gerhard J. (Environmental Microbiology, 2009)
Prokaryotic extracellular enzymatic activity, abundance, heterotrophic production and respiration were determined in the meso‐ and bathypelagic (sub)tropical North Atlantic. While prokaryotic heterotrophic production (PHP) decreased from the lower euphotic layer to the bathypelagic waters by two orders of magnitude, prokaryotic abundance and cell‐specific PHP decreased only by one order of magnitude. In contrast to cell‐specific PHP, cell‐specific extracellular enzymatic activity (alpha‐ and beta‐glucosidase, leucine aminopeptidase, alkaline phosphatase) increased with depth as did cell‐specific respiration rates. Cell‐specific alkaline phosphatase activity increased from the intermediate water masses to the deep waters up to fivefold. Phosphate concentrations, however, varied only by a factor of two between the different water masses, indicating that phosphatase activity is not related to phosphate availability in the deep waters. Generally, cell‐specific extracellular enzymatic activities were inversely related to cell‐specific prokaryotic leucine incorporation. Thus, it is apparent that the utilization of deep ocean organic matter is linked to higher cell‐specific extracellular enzymatic activity and respiration and lower cell‐specific PHP than in surface waters. 2014 1998 4,909 Q1 SCIE